Diamond-max ceramics bonding phase composites – phases and microstructure analysis - Jaworska, L.; Klimczyk, P.; Putyra, P.; Rozmus, M.; Bucko, M.; Morgiel, J.; Stobierski, L. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2011)
The possibility for improving the thermal stability of polycrystalline materials based on diamond (PCD) is to reduce the content of cobalt. Diamond compacts without cobalt phases with Ti3₃iC₂ і Cr₂AlC prepared using the method of self-propagating high-temperature synthesis (SHS). The resulting compacts with 20 wt. % of the above phases were exposed to high pressure and temperature in order to further consolidate the structure by sintering. Sintering was performed at 8±0.2 GPa and 1950±50 °C. Phase composition and microstructural study of the original compacts and the composites made by X-ray diffraction (XRD) and scanning electron microscopy (SEM). Одна з можливостей підвищення термостійкості полікристалічних матеріалів на основі алмазу (PCD) полягає в зменшенні вмісту в них кобальту. Алмазні компакти без кобальту з фазами Ti3₃iC₂ і Cr₂AlC отримували з використанням методу само поширюваного високотемпературного синтезу (SHS). Отримані компакти з 20 мас. % зазначених фаз піддавали дії високого тиску і температури з метою подальшої консолідації структури шляхом спікання. Процес спікання здійснювали при 8 ± 0,2 ГПа и 1950 ± 50 °С. Фазовий склад і мікроструктурні дослідження вихідних компактів і отриманих композитів виконані методами рентгенівської дифрактометрії (XRD) і скануючої електронної мікроскопії (SEM). Одна из возможностей повышения термостойкости поликристаллических материалов на основе алмаза (PCD) заключается в снижении содержания в них кобальта. Алмазные компакты без кобальта с фазами Ti3₃iC₂ и Cr₂AlC получали с использованием метода самораспространяющегося высокотемпературного синтеза (SHS). Полученные компакты с 20 % по мас. указанных фаз подвергали воздействию высокого давления и температуры с целью дальнейшей консолидации структуры путем спекания. Процесс спекания осуществляли при 8 ± 0,2 ГПа и 1950 ± 50 °С. Фазовый состав и микроструктурные исследования исходных компактов и полученных композитов выполнены методами рентгеновской дифрактометрии (XRD) и сканирующей электронной микроскопии (SEM).